Fermi-surface topology and the effects of intrinsic disorder in a class of charge-transfer salts containing magnetic ions, β''-(BEDT-TTF)_4[(H_3O)M(C_2O_4)_3]Y - Coldea, A; Bangura, A; Singleton, J; Ardavan, A; Akutsu-Sato, A; Akutsu, H; Turner, S; Day, P (2003)
We report high-field magnetotransport measurements on β''-(BEDT-TTF)_4[(H_3O)M(C_2O_4)_3]Y, where M=Ga, Cr and Fe and Y=C_5H_5N. We observe similar Shubnikov-de Haas oscillations in all compounds, attributable to four quasi-two-dimensional Fermi-surface pockets, the largest of which corresponds to a cross-sectional area ~8.5% of the Brillouin zone. The cross-sectional areas of the pockets are in agreement with the expectations for a compensated semimetal, and the corresponding effective masses are ~m_e, rather small compared to those of other BEDT-TTF salts. Apart from the case of the smallest Fermi-surface pocket, varying the $M$ ion seems to have little effect on the overall Fermi-surface topology or on the effective masses. Despite the fact that all samples show quantum oscillations at low temperatures, indicative of Fermi liquid behavior, the sample- and temperature-dependence of the interlayer resistivity suggest that these systems are intrinsically inhomogeneous. It is thought that intrinsic tendency to disorder in the anions and/or the ethylene groups of the BEDT-TTF molecules leads to the coexistence of insulating and metallic states at low temperatures; comparison with other charge-transfer salts suggests that this might be a rather general phenomenon. A notional phase diagram is given for the general family of β''-(BEDT-TTF)_4[(H_3O)M(C_2O_4)_3]Y salts, which exhibits several marked similarities with that of the κ-(BEDT-TTF)_2X superconductors.